2022
DOI: 10.21512/commit.v16i1.7583
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty of Shopee on Consumers’ Purchasing Decisions

Abstract: Shopping through e-commerce is one of the new tools in the current era. Various brands offer the large selection of products or services making shopping through e-commerce like shopping in the city center, but online. Currently, many e-commerce companies are running similar services because e-commerce is important to build a strong brand from the audience and shows the value of the products or services they offer. The aim of the research is to see how significant the influence of Shopee’s brand equity is on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 0 publications
3
9
0
2
Order By: Relevance
“…This is supported by the T-Statistic value showing 6.361 which is greater than 1.96 and the P-Values value showing 0.000 which is smaller than 0.05. This is in line with research conducted by (Supiyandi, Hastjarjo, & Slamet, 2022) which states that the variable that has the most influence on purchasing decisions is brand loyalty of all the variables used. In other words, increased brand loyalty will greatly influence purchasing decisions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is supported by the T-Statistic value showing 6.361 which is greater than 1.96 and the P-Values value showing 0.000 which is smaller than 0.05. This is in line with research conducted by (Supiyandi, Hastjarjo, & Slamet, 2022) which states that the variable that has the most influence on purchasing decisions is brand loyalty of all the variables used. In other words, increased brand loyalty will greatly influence purchasing decisions.…”
Section: Discussionsupporting
confidence: 89%
“…From research by (Supiyandi, Hastjarjo, & Slamet, 2022) states that the variable that has the most influence on purchasing decisions is brand loyalty of all the variables mentioned used. In other words, increased brand loyalty will greatly influence purchasing decisions.…”
Section: Hypothesis 5 (H5): the Influence Of Brand Loyalty On Consume...mentioning
confidence: 99%
“…The purchase decision is conceptualised as the user's resolve to acquire a product for a specific purpose within a particular period (Chenting & Yue, 2020). Given the forgoing narrative, it can be suggested that purchase decisions can be influenced by key antecedents such as perceived quality, brand loyalty, price (Koech et al, 2023;Mustaghfirin & Ariyanti, 2023;Supiyandi et al, 2022;Walia & Kumar, 2022) as well as the quality of retail services and timing of delivery (Alrawad et al, 2023;Anbumathi et al, 2023). Domingos et al (2022) have argued that purchase decision is associated with the consumer's purchase behaviour which subsequently leads to actual purchase.…”
Section: Introductionmentioning
confidence: 99%
“…Customer satisfaction and interest in continuing to buy can be measured by fulfilling the sales target achievement of each retailer. Customer decisions in certain online purchases are influenced by brand loyalty and the customer experience in using the services provided, as they have close ties to certain services or brands [14].…”
Section: Introductionmentioning
confidence: 99%